IN THE WAKE OF COVID-19: REFLECTING ON SOCIAL WORK’S CLIMATIC FUTURE - Leduc, Timothy (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2022)
We have moved into an era some call the Anthropocene, a time when nothing is untouched by the seeming unending expansion of modern systems (political, economic, cultural, virtual) and their inevitable global impacts. In many ways, COVID-19 intensified our awareness of this global interconnectivity not only through contact-tracing the pandemic, but also through its varied impacts on modern systems that further highlighted our ongoing dance with global and local environmental changes. The interconnected nature of our climate of change is revealing to us the partial, dualistic and ultimately limited modern worldview that continues to constrict the social justice principles our vocation of social work holds as its ideal. Something is out of balance and we need to work upon this imbalance in ways that do not deny the loss, confusion, injustices and power-grabs highlighted in the wake of COVID-19. Through approaching our climate of change in this way, we are given an opportunity to reflect on social distancing in relation to honouring boundaries, the value of slowing down modern ways of living, and the need to look more closely at our modern blocks to a sustainable future on planet Earth; in other words our climatic truth-work. In this article, I reflect on what Canadian society, the social work profession and the international community have learned (or not learned) from the pandemic about the climate of cultural change before us.